Antimetabolite pemetrexed primes a favorable tumor microenvironment for immune checkpoint blockade therapy - Lu, Chia-Sing; Lin, Ching-Wen; Chang, Ya-Hsuan; Chen, Hsuan-Yu; Chung, Wei-Chia; Lai, Wei-Yun; Ho, Chao-Chi; Wang, Tong-Hong; Chen, Chi-Yuan; Yeh, Chen-Lin; Wu, Sean; Wang, Shu-Ping; et al. (Journal for immunotherapy of cancer, 2020)
BackgroundThe immune checkpoint blockade (ICB) targeting programmed cell death-1 (PD-1) and its ligand (PD-L1) has been proved beneficial for numerous types of cancers, including non-small-cell lung cancer (NSCLC). However, a significant number of patients with NSCLC still fail to respond to ICB due to unfavorable tumor microenvironment. To improve the efficacy, the immune-chemotherapy combination with pemetrexed, cis/carboplatin and pembrolizumab (anti-PD-1) has been recently approved as first-line treatment in advanced NSCLCs. While chemotherapeutic agents exert beneficial effects, the underlying antitumor mechanism(s) remains unclear.MethodsPemetrexed, cisplatin and other chemotherapeutic agents were tested for the potential to induce PD-L1 expression in NSCLC cells by immunoblotting and flow cytometry. The ability to prime the tumor immune microenvironment was then determined by NSCLC/T cell coculture systems and syngeneic mouse models. Subpopulations of NSCLC cells responding differently to pemetrexed were selected and subjected to RNA-sequencing analysis. The key signaling pathways were identified and validated in vitro and in vivo.ResultsPemetrexed induced the transcriptional activation of PD-L1 (encoded by CD274) by inactivating thymidylate synthase (TS) in NSCLC cells and, in turn, activating T-lymphocytes when combined with the anti-PD-1/PD-L1 therapy. Nuclear factor κB (NF-κB) signaling was activated by intracellular reactive oxygen species (ROSs) that were elevated by pemetrexed-mediated TS inactivation. The TS−ROS−NF-κB regulatory axis actively involves in pemetrexed-induced PD-L1 upregulation, whereas when pemetrexed fails to induce PD-L1 expression in NSCLC cells, NF-κB signaling is unregulated. In syngeneic mouse models, the combinatory treatment of pemetrexed with anti-PD-L1 antibody created a more favorable tumor microenvironment for the inhibition of tumor growth.ConclusionsOur findings reveal novel mechanisms showing that pemetrexed upregulates PD-L1 expression and primes a favorable microenvironment for ICB, which provides a mechanistic basis for the combinatory chemoimmunotherapy in NSCLC treatment.